2017
DOI: 10.1016/j.jcomdis.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Vocalic transitions as markers of speech acoustic changes with STN-DBS in Parkinson’s Disease

Abstract: Purpose Deep Brain Stimulation of the subthalamic nucleus (STN-DBS) effectively treats cardinal symptoms of idiopathic Parkinson’s disease (PD) that cannot be satisfactorily managed with medication. Research is equivocal regarding speech changes associated with STN-DBS. This study investigated the impact of STN-DBS on vocalic transitions and the relationship to intelligibility. Methods Eight Quebec-French speakers with PD and eight healthy controls participated. The slope of the second formant frequency (F2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 56 publications
1
9
0
3
Order By: Relevance
“…Previous studies reported mixed results for a variety of acoustic metrics. For example, for STN-DBS patients after DBS implantation, studies have reported significant increases in overall loudness ( Tripoliti et al, 2011 ), significant increases in vowel space areas ( Tanaka et al, 2016 ), and non-significant changes in second formant slopes ( Martel-Sauvageau and Tjaden, 2017 ), with stimulation on compared to stimulation off. Overall, the lack of systematic stimulation or group differences in acoustic outcomes prevents wider conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported mixed results for a variety of acoustic metrics. For example, for STN-DBS patients after DBS implantation, studies have reported significant increases in overall loudness ( Tripoliti et al, 2011 ), significant increases in vowel space areas ( Tanaka et al, 2016 ), and non-significant changes in second formant slopes ( Martel-Sauvageau and Tjaden, 2017 ), with stimulation on compared to stimulation off. Overall, the lack of systematic stimulation or group differences in acoustic outcomes prevents wider conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to which nucleus is targeted, the following factors must be considered: behavioral measure (acoustic vs. intelligibility vs. self-perception outcomes); medication state (OFF vs. ON); electrode location within the target nucleus (e.g., anterior vs. posterior STN); stimulation parameters (low vs. high intensity and frequency); volume of neural tissue affected by the electrode current; and timescale of effects (immediate vs. gradual). The heterogeneity of behavioral measures across studies alone makes interpreting the effects of DBS challenging; some studies report acoustic parameters ( D'Alatri et al, 2008 ; Van Lancker Sidtis et al, 2010 ; Karlsson et al, 2013 ; Martel-Sauvageau and Tjaden, 2017 ) while others focus on intelligibility ratings ( Tornqvist et al, 2005 ; Tripoliti et al, 2011 ; Chiu et al, 2020 ) or self-perceived speech ratings ( Miller et al, 2006 ; Wertheimer et al, 2014 ; Kopf et al, 2022 ). Furthermore, two different time windows of effects of stimulation should not be conflated: (a) acute intraoperative microelectrode stimulation mapping or DBS lead stimulation after it’s turned on in the weeks after surgery, and (b) long-term (months to years) cumulative effects of brain stimulation.…”
Section: Effects Of Pharmacological and Surgical Treatments For Pd On...mentioning
confidence: 99%
“…A raíz de aquello, se han efectuado en varias lenguas estudios fonético-acústicos que contrastan las vocales entre hablantes con EP y sujetos sin la enfermedad, tales como, inglés norteamericano (Forrest et al, 1989;Kim et al, 2009;Kim y Choi, 2017;McRae et al, 2002;Rosen et al, 2006;Tjaden et al, 2013;Tjaden y Wilding, 2004;Weismer et al, 2001;Whitfield y Goberman, 2014), coreano (Bang et al, 2013;Kang et al, 2010;Kim y Choi, 2017;Shim et al, 2012), alemán (Skodda et al, 2011(Skodda et al, , 2012(Skodda et al, , 2013, checo (Rusz, Cmejla, Růžičková, et al, 2013;Rusz, Cmejla, Tykalova, et al, 2013), chino mandarín (Gu et al, 2018;Hsu et al, 2017), español peninsular (Fernández-García et al, 2021), español cubano (Aguilera et al, 2015;Escobedo et al, 2017), italiano (Vizza et al, 2019), francés canadiense (Martel-Sauvageau y Tjaden, 2017) y portugués europeo (Proença et al, 2014). En ellos, los hablantes con EP tendieron a exhibir una menor duración de las transiciones de los formantes (Forrest et al, 1989), una menor extensión de las transiciones de los formantes (Forrest et al, 1989), una menor pendiente del segundo formante (F2) (Kim et al, 2009;Martel-Sauvageau y Tjaden, 2017;Rosen et al, 2006), un menor primer formante (F1) de /a/ (Bang et al, 2013), un mayor F1 de /i/ (Bang et al, 2013;Escobedo et al, 2017), un menor F2 de /i/ (Bang et al, 2013;…”
unclassified